(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The teaching profession demands significant time, emotional involvement, and professional commitment, which often create conflicts between work and family responsibilities. This study examines Work Interference with Family (WIF) and Family Interference with Work (FIW) among college teachers. The study aims to understand the extent to which professional responsibilities affect family life and how family responsibilities influence work performance. Data were collected from 340 college teachers through a structured questionnaire using convenient sampling techniques. The findings reveal that heavy workload, administrative responsibilities, extended working hours, and family obligations significantly contribute to work-family conflicts. The study highlights the importance of flexible work policies, stress management practices, and institutional support systems to improve work-life balance among college teachers.